Facile synthesis of nitrogen-defective g-C3N4 for superior photocatalytic degradation of rhodamine B. Issue 49 (14th September 2021) - Yang, Xiupei; Zhang, Lin; Wang, Dan; Zhang, Qian; Zeng, Jie; Zhang, Run
Abstract : Nitrogen-defective g-C3 N4 is synthesized and characterized as the photocatalyst for degradation of organic dyes, such as rhodamine B, in wastewater. Abstract : Developing a new photocatalyst for fast and highly efficient organic dye degradation plays an essential role in wastewater treatment. In this study, a photocatalyst graphite phase carbon nitride (g-C3 N4 ) containing nitrogen defects (CN) is reported for the degradation of rhodamine B (RhB). The porous g-C3 N4 photocatalyst is facilely synthesized through a polycondensation method and then characterized by X-ray diffraction (XRD), infrared spectroscopy (FT-IR), field emission scanning electron microscopy (FESEM), N2 isotherm adsorption line, and X-ray photoelectron spectroscopy (XPS). The photocatalytic activity of the g-C3 N4 is evaluated through the degradation of RhB under visible light irradiation. The results show that photocatalytic activity of the nitrogen-defective g-C3 N4 can be improved by optimizating washing conditions, including washing temperature, washing dosage, drying time, and drying temperature. With the prepared nitrogen-defective g-C3 N4, decolourization of RhB is able to be completed within 20 minutes, in which the degradation rate is 1.7 times higher than that of bulk g-C3 N4 . Moreover, the nitrogen-defective g-C3 N4 has high stability and reusability in the degradation of RhB. Photocatalytic degradation mechanism investigations by ultraviolet-visible absorption spectroscopy, radical trapping experiments and high-performance liquid chromatography (HPLC) reveal that RhB achieved complete mineralization through the photocatalytic degradation reaction mediated by superoxide radicals (˙O2 − ). This work thus provides a new approach for the preparation of photocatalysts for organic pollutants treatment in wastewater samples.